Modeling and development of a decision support system for supplier selection in the process industry - Pandian Pichipoo; Ponnusamy Venkumar; Sivaprakasam Rajakarunakaran (Journal of Industrial Engineering International, 2013)
This paper presents the development of a model based decision support system with a case study on solving the supplier selection problem in a chemical processing industry. For the evaluation and selection of supplier, the analytical hierarchy process (AHP) and grey relational analysis (GRA) were used. The intention of the study is to propose an appropriate platform for process industries in selecting suppliers, which was tested with an electroplating industry during the course of development. The sensitivity analysis was performed in order to improve the robustness of the results with regard to the relative importance of the evaluation criteria and the parameters of the evaluation process. Finally, a practical implementation study was carried out to reveal the procedure of the proposed system and identify the suitable supplier with detailed discussions about the benefits and limitations.
Keywords: 650; Supplier evaluation; Supplier selection; Model base; Decision support system; Analytical hierarchy process; Grey relational analysis